Variational approach to dynamics of bright solitons in lossy optical fibers - M. F. Mahmood; S. Brooks (International Journal of Mathematics and Mathematical Sciences)
A variational analysis of dynamics of soliton solution of coupled nonlinear Schrödinger equations with oscillating terms is made, considering a birefringent fiber with a third-order nonlinearity in the anomalous dispersion frequency region. This theoretical model predicts optical soliton oscillations in lossy fibers.